Life after growth how the global economy really works and why 200 years of growth are over - Morgan, Tim. (Hampshire Harriman House, 2013)
Why, years after the banking crisis, is the global economy still mired in recession and burdened by enormous debts? Why have the tried-and-tested economic policies of the past failed us this time?
Includes index
Keywords: Global economy